2021
DOI: 10.3390/cmd2040039
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness of Different Ageing Conditions for Three Thick Marine Epoxy Systems

Abstract: Three different coated steel systems were aged in natural or artificial seawater, in neutral salt spray (NSS), and using alternate immersion tests in order to evaluate the aggressiveness of the different ageing conditions. Commercial epoxy coatings were applied onto steel (S355NL), hot-galvanized steel (HDG), and Zn-Al15 thermal spraying coated steel. The defect-free systems were immersed in artificial seawater at 35 °C for 1085 days and in natural seawater for 1200 days and were characterized by electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…However, after studying different tests' parameters (type of environmental stresses, presence of scribe, etc. ), Renaud et al concluded that the presence of an artificial defect was needed to properly rank these types of systems [39]. Thus, an open discussion exists in the scientific community about the best way to assess the performance of marine coatings.…”
Section: Site Comparisonmentioning
confidence: 99%
“…However, after studying different tests' parameters (type of environmental stresses, presence of scribe, etc. ), Renaud et al concluded that the presence of an artificial defect was needed to properly rank these types of systems [39]. Thus, an open discussion exists in the scientific community about the best way to assess the performance of marine coatings.…”
Section: Site Comparisonmentioning
confidence: 99%